Economic Survey of Latin America and the Caribbean 2000-2001 - Economic Commission for Latin America; the Caribbean (United Nations, 2001)
This survey presents an overview of the regional economy and the economic performance in 2000 and the first half of 2001. It also offers individual country reports on the performance of the 20 countries of Latin America for the same period. In addition, the Economic Survey of Latin America and the Caribbean analyzes the economic situation in the countries of the English-speaking Caribbean. This year's edition includes a CD-ROM that contains the statistical appendix.